(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article discusses whether philosophical thought moves from the analysis of the “mythological roots” of art to its later forms or, conversely, from the latest works of art to the mythological paradigm in them - in both cases, as we see, we are talking about the construction of a new - artificial, in contrast to the previous ones, which developed naturally - myth. Some of the newest trends in Western European philosophy and art, seeing the only anchor for the salvation of culture in a “godless world”, show an infinite attraction to it.